Infrared measurements of column abundances of several trace gases in the Antarctic atmosphere - Murcray, F. J.; Murcray, F. H.; Murcray, D. G. (1988)
Atmospheric emission measurements were made in 1978 from an LC 130 aircraft from Point Mugu, CA, to McMurdo Station, Antarctica, and from McMurdo over the Antarctic continent on several different flights. These included a number of flights over the South Pole. In December 1980, infrared solar spectra were obtained from the ground at South Pole Station. Infrared solar spectra were also obtained from South Pole during late November and early December of 1986. These latter measurements were extended to cover additional spectral regions to obtain column densities of a number of additional constituents. The results obtained from these measurement series are reviewed and, where measurements were made during both periods, compared. Spectral absorption or emission features due to HNO3, NO, NO2, HCl, (H-16)2O, (H-18)2O, HDO, CH4, and N2O were used to obtain data on the total column abundances for these compounds.